Microsoft Windows server 2008 administration - Seguis, Steve (New York : McGraw-Hil, 2008)
Exploit the powerful management, networking, and security tools in Windows Server 2008 using the comprehensive information contained in this real-world resource. Written by a seasoned Windows systems engineer, Microsoft Windows Server 2008 Administration lays out each feature alongside clear explanations, practical examples, and hands-on exercises. Inside, you'll learn how to deploy Windows Server 2008, use the new, integrated Server Manager tool, handle Internet services and remote access, and fine-tune performance. You'll also learn how to automate administrative tasks, create reliable system backups, and harden your server's defenses. Perform typical and Server Core installations of Windows Server 2008 Modify system and component settings using the new Server Manager Administer users, groups, and computers with Active Directory Deliver robust web and FTP hosting using IIS 7.0 and ASP.NET Monitor stability and performance with Windows System Resource Manager Manage security using NAP, IPSec, 802.1x, and DHCP enforcement Encrypt data with Active Directory Certification Services and PKI Provide secure remote access using Terminal Services and RRAS Handle Windows DNS, BitLocker Drive Encryption, and Itanium support Build Windows PowerShell scripts to perform repetitive management jobs
Chapter 1 : Getting Started with Windows Server 2008 -- Chapter 2 : Server Core -- Chapter 3 : Server Manager -- Chapter 4 : Active Directory Domain Services -- Chapter 5 : Windows Deployment Services -- Chapter 6 : Internet Information Services 7 0 -- Chapter 7 : Resource Management and Performance Monitoring -- Chapter 8 : Network Policy and Access Services -- Chapter 9 : Terminal Services -- Chapter 10 : Windows DNS, BitLocker Drive Encryption, and Itanium Support -- Chapter 11 : Routing and Remote Access -- Chapter 12 : Enterprise Public Key Infrastructure -- Chapter 13 : Windows PowerShell.
Includes index.
1
Keywords: Microsoft Windows server; Operating systems (Computers)